Ultra‐performance LC‐ESI/quadrupole‐TOF MS for rapid analysis of chemical constituents of Shaoyao‐Gancao decoction. Issue 7 (12th March 2013) - Yin, Quanwei; Wang, Ping; Zhang, Aihua; Sun, Hui; Wu, Xiuhong; Wang, Xijun
<x xml:space="preserve">Abstract</x> Shaoyao–Gancao decoction (SGD), a traditional Chinese formulae containing Paeoniae Radix and Glycyrrhizae Radix, is commonly used to relieve abdominal pain. It has attracted increasingly much attention as one of the most popular and valuable herbal medicine in clinic. However, the systematic analysis of chemical constituents of SGD are difficult to determine and thus remain unclear. In this paper, a rapid, sensitive, and reliable ultra‐performance LC‐ESI/quadrupole‐TOF high‐definition MS (UPLC‐ESI‐Q‐TOF‐MS) with automated MetaboLynx analysis in negative ion mode were established to characterize the chemical constituents of SGD. The analysis was performed on a Waters UPLCTM HSS T3 (2.1 × 100 mm, 1.8 μm) using gradient elution system. MS/MS fragmentation behavior was proposed for aiding the structural identification of the components. With the optimized conditions, a total of 58 peaks were tentatively characterized by comparing the retention time and mass spectrometry data and retrieving the reference literatures. Of note, 44 ingredients were identified from Glycyrrhizae Radix, and 14 were from Paeoniae Radix. It is concluded that a rapid and robust platform based on UPLC‐ESI‐Q‐TOF‐MS was successfully developed for globally identifying multiple‐constituent of traditional Chinese medicine prescriptions. This is the first report on systematic analysis of chemical constituents and in vivo metabolites of SGD.